2019
DOI: 10.1186/s40494-019-0344-0
|View full text |Cite
|
Sign up to set email alerts
|

Beauty is skin deep: the skin tones of Vermeer’s Girl with a Pearl Earring

Abstract: The soft modelling of the skin tones in Vermeer's Girl with a Pearl Earring (Mauritshuis) has been remarked upon by art historians, and is their main argument to date this painting to c. 1665. This paper describes the materials and techniques Vermeer used to accomplish the smooth flesh tones and facial features of the Girl, which were investigated as part of the 2018 Girl in the Spotlight research project. It combines macroscopic X-ray fluorescence imaging (MA-XRF), reflectance imaging spectroscopy (RIS), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 20 publications
(35 reference statements)
4
39
0
Order By: Relevance
“…Additional findings about the type of lead white and binding medium were made using analytical techniques that are not reported in this paper. Lead isotope analysis found that the lead ore in the ground was consistent with other Northern paintings, and came from a British source [6]. Micro X-ray powder diffraction (µXRPD) of cross-sections established that the average hydro cerussite to cerussite ratio is estimated as 0.88 ± 0.04, which is typical for Dutch stack process lead white [5].…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Additional findings about the type of lead white and binding medium were made using analytical techniques that are not reported in this paper. Lead isotope analysis found that the lead ore in the ground was consistent with other Northern paintings, and came from a British source [6]. Micro X-ray powder diffraction (µXRPD) of cross-sections established that the average hydro cerussite to cerussite ratio is estimated as 0.88 ± 0.04, which is typical for Dutch stack process lead white [5].…”
Section: Discussionmentioning
confidence: 68%
“…Micro X-ray powder diffraction (µXRPD) of cross-sections established that the average hydro cerussite to cerussite ratio is estimated as 0.88 ± 0.04, which is typical for Dutch stack process lead white [5]. Fourier transform infrared-attenuated total reflectance spectroscopy (FTIR-ATR) analysis confirmed the presence of chalk, lead white and a drying oil in the ground [6,7]. A fragment was analysed using thermally assisted hydrolysis and methylation, pyrolysis gas chromatography-mass spectrometry (THM-Py-GC/MS), which determined that the binding medium of the ground is linseed oil.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…the leftlit-side of the face), the MA-XRF iron map shows less emission intensity from iron, even though iron ochre was identified in the reflectance/first derivative spectra. A cross-section from the forehead [12] identified a small amount of iron ochre in the surface layer, and more iron ochre in the sub-surface layer beneath the mercury-and lead-containing paint. Hence, the low intensity of iron in this region in the MA-XRF map could be the result of mercury and lead absorbing some of the X-ray excitation irradiance, thus effectively reducing the amount of iron that is excited.…”
Section: Skin and Lipsmentioning
confidence: 99%